Component-based network systems engineering - Norris, Mark (Artech House telecommunications library., 2000)
"The book explores interfaces, integration, components, and architectures; explains how these elements relate; and helps you determine the combinations and approaches that will yield the best results for your organization's needs. You get hands-on guidance to building systems based upon real-world experience and solid network engineering theory without getting bogged down in technological complexity."--Jacket.